Composition and preparation method thereof
By using an oxygen-resistance sealant composed of butyl rubber, polyisobutylene composition and the like on the back panel of the solar cell, the problem of poor barrier effects of water vapor and oxygen in the prior art is solved, and higher weather resistance and The barrier effect extends the life of photovoltaic modules.
Patent Information
- Application Number
- CN202411614863.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing solar cell back panel has poor barrier effect on water vapor and oxygen, resulting in bubbles, yellowing, delamination and other phenomena in high temperature and high humidity environments, affecting the efficiency and life of photovoltaic modules.
A composition is adopted, which includes butyl rubber, polyisobutylene composition, thermoplastic elastomer, reinforcement material, inorganic filler, barrier filler, coupling agent, light stabilizer and antioxidant, by different molecular weight polyisobutylene and butyl The base rubber is compounded, and materials such as reducing iron powder and molecular sieve are added to form an oxygen-resisting composition, and kneaded under nitrogen protection. The stirring time is strictly controlled to reduce the contact between the material and water vapor and oxygen.
It achieves excellent water-oxygen barrier properties and weather resistance, effectively alleviates the erosion of oxygen on solar modules and extends the life of the modules. At the same time, the method is safe and environmentally friendly and suitable for industrial production.
Smart Images

Figure BDA0005131911700000031 
Figure BDA0005131911700000032 
Figure BDA0005131911700000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and relates to a composition and a preparation method thereof, in particular to an oxygen-barrier hot-melt sealant and a preparation method thereof. Background Art
[0002] Butyl sealant is mainly composed of butyl rubber, plasticizer, tackifying resin and filler. Compared with silicone sealant, it is widely used for sealing and waterproofing because of its inherent excellent low water vapor permeability. However, with the development of solar energy manufacturing and the research and development of new components, higher requirements are placed on the performance of packaging materials, especially the instability of the perovskite absorption layer and the easy degradation of the battery due to water vapor intrusion. Therefore, this type of new battery material is more sensitive to water vapor and requires better moisture protection, otherwise water vapor will have an adverse effect on the output power and service life of the component.
[0003] The existing solar cell backsheet has poor barrier effect against water vapor and oxygen. When the backsheet is exposed to high temperature and high humidity for a long time, bubbles, yellowing, delamination and other phenomena will occur, which will significantly reduce the photoelectric conversion efficiency of photovoltaic modules. When oxygen enters the module, it will react with reducing substances such as metal components and active hydrogen to produce redox reactions. When the cell is exposed to high temperature, high humidity and high ultraviolet radiation outdoors for a long time, it will be oxidized, the resistance of the module will increase, and the risk of internal material aging will increase, which will in turn affect the power generation efficiency and service life of the photovoltaic module.
[0004] Therefore, there is an urgent need for a material that has good oxygen barrier and waterproof effects while meeting the existing photovoltaic lamination and packaging processes, which can effectively alleviate the erosion of oxygen on solar panels and effectively extend their lifespan. Summary of the invention
[0005] The purpose of the present invention is to provide a composition with excellent weather resistance and water and oxygen barrier properties and a preparation method thereof in view of the deficiencies in the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The first object of the present invention is to provide a composition, wherein the raw materials for preparing the composition include the following components: butyl rubber, polyisobutylene composition, thermoplastic elastomer, reinforcing material, inorganic filler, barrier filler, coupling agent, light stabilizer and antioxidant;
[0008] Wherein, the thermoplastic elastomer is selected from one or a combination of SEBS, SEPS, EVOH and POE;
[0009] The barrier filler is selected from reduced iron powder and / or molecular sieve.
[0010] Preferably, the thermoplastic elastomer is EVOH and / or POE.
[0011] Preferably, the thermoplastic elastomer is a combination of EVOH and POE.
[0012] Preferably, the weight ratio of EVOH to POE is 1:(0.1-2), preferably 1:(0.5-1.5);
[0013] Preferably, the ethylene content in the EVOH is 25 to 35% by mass.
[0014] Preferably, the molecular sieve is from 3A to 5A molecular sieve.
[0015] Preferably, the weight ratio of the reduced iron powder to the molecular sieve is 1:(0.1-1), preferably 1:(0.5-1).
[0016] Preferably, the polyisobutylene composition comprises high molecular weight polyisobutylene and medium molecular weight polyisobutylene;
[0017] Preferably, the number average molecular weight of the high molecular weight polyisobutylene is 500,000 to 2,000,000, and the number average molecular weight of the medium molecular weight polyisobutylene is 10,000 to 300,000.
[0018] Preferably, the weight ratio of the high molecular weight polyisobutylene to the medium molecular weight polyisobutylene is 1:(1-10), preferably 1:(3-8).
[0019] Preferably, the reinforcing material includes one or a combination of carbon black, fumed silica, and nano calcium carbonate.
[0020] More preferably, the reinforcing material is carbon black.
[0021] Preferably, the inorganic filler includes one or a combination of microsilica powder, talc, organic bentonite and nano calcium carbonate.
[0022] More preferably, the inorganic filler is one or a combination of microsilica powder, talcum powder, and organic bentonite.
[0023] In a preferred example, the inorganic filler is a combination of microsilica powder, talcum powder, and organic bentonite.
[0024] Preferably, the weight ratio of the microsilica powder, talc and organic bentonite is 1:(0.5-2):(0.5-2), preferably 1:(1-2):(0.5-1.5).
[0025] Preferably, the coupling agent is a silane coupling agent.
[0026] Further preferably, the coupling agent is one or a combination of vinyl silane coupling agent, methoxy silane coupling agent or isocyanate silane coupling agent.
[0027] In a preferred example, the coupling agent is an isocyanate silane coupling agent.
[0028] Preferably, the content of the butyl rubber is 5 to 20 parts by weight.
[0029] More preferably, the content of the butyl rubber is 5 to 15 parts.
[0030] Preferably, the content of the polyisobutylene composition is 15 to 35 parts by weight.
[0031] More preferably, the content of the polyisobutylene composition is 15 to 30 parts.
[0032] Preferably, the content of the thermoplastic elastomer is 5 to 20 parts by weight.
[0033] More preferably, the content of the thermoplastic elastomer is 5 to 15 parts.
[0034] Preferably, the content of the reinforcing material is 1 to 10 parts by weight.
[0035] More preferably, the content of the reinforcing material is 2 to 8 parts.
[0036] Preferably, the content of the inorganic filler is 40 to 55 parts by weight.
[0037] More preferably, the content of the inorganic filler is 40 to 50 parts.
[0038] Preferably, the content of the barrier filler is 2 to 10 parts by weight.
[0039] More preferably, the content of the barrier filler is 5 to 10 parts.
[0040] Preferably, the content of the coupling agent is 0.1 to 2 parts by weight.
[0041] More preferably, the content of the coupling agent is 0.5 to 1.5 parts.
[0042] Preferably, the content of the light stabilizer is 0.1 to 1 part by weight.
[0043] More preferably, the content of the light stabilizer is 0.1 to 0.8 parts.
[0044] Preferably, the content of the antioxidant is 0.1 to 1 part by weight;
[0045] More preferably, the content of the antioxidant is 0.1 to 0.8 parts.
[0046] Preferably, the raw materials for preparing the composition include: butyl rubber, high molecular weight polyisobutylene, medium molecular weight polyisobutylene, EVOH, POE, organic bentonite, talc, microsilica powder, carbon black, reduced iron powder, 3A molecular sieve, coupling agent, light stabilizer and antioxidant;
[0047] Preferably, the raw materials for preparing the composition consist of butyl rubber, high molecular weight polyisobutylene, medium molecular weight polyisobutylene, EVOH, POE, organic bentonite, talc, microsilica powder, carbon black, reduced iron powder, 3A molecular sieve, coupling agent, light stabilizer and antioxidant.
[0048] Further preferably, the raw materials for preparing the composition include:
[0049]
[0050] Further preferably, the raw materials for preparing the composition include:
[0051]
[0052]
[0053] The second object of the present invention is to provide a method for preparing the composition as described in any one of the above items, the preparation method comprising the following steps:
[0054] (1) adding butyl rubber, polyisobutylene composition, and thermoplastic elastomer into a kneader according to weight proportions, heating, and kneading under the protection of an inert gas, and then adding a reinforcing material, an inorganic filler, a light stabilizer, and an antioxidant into the kneader and continuing to knead;
[0055] (2) Then, the coupling agent and barrier filler are added to the mixture obtained in step (1), the inert gas is turned off, and the mixture is evacuated for kneading, and the vacuum degree is controlled to be 0.08-0.1 MPa.
[0056] Preferably, before step (1), the inorganic filler, the reinforcing material and the barrier filler are first dried and dehydrated.
[0057] Preferably, the kneading temperature in step (1) is controlled to be 140-160° C. and the rotation speed is 20 r / min.
[0058] Preferably, the kneading time in step (1) is controlled to be 25 to 35 minutes, preferably 30 minutes.
[0059] Preferably, the kneading temperature in step (2) is controlled to be 140-160° C. and the rotation speed is 30 r / min.
[0060] Preferably, the kneading time in step (2) is controlled to be 35 to 45 minutes, preferably 40 minutes.
[0061] The third object of the present invention is to provide an application of the composition described above or the composition obtained according to the preparation method described above in oxygen-barrier hot-melt sealant.
[0062] Effects of the Invention
[0063] The invention increases the initial viscosity, bonding force and relatively high bulk strength of the polymer by compounding polyisobutylene with different molecular weights and butyl rubber, adds reduced iron powder, activated carbon and other materials to form an oxygen barrier composition, and removes a small amount of oxygen entering the component; adding compounded thermoplastic elastomers such as EVOH resin and POE resin can improve the weather resistance of the photovoltaic component; the sealant preparation method provided by the invention is operated under nitrogen protection, and the stirring time is strictly controlled to reduce the contact time between the material and water vapor and oxygen; the stirring in the preparation method provided by the invention is physical stirring and mixing, and no organic waste gas and waste liquid are generated during the preparation and use of the sealant, which is safe, environmentally friendly and conducive to industrial production. DETAILED DESCRIPTION
[0064] In order to make the technical solutions and beneficial effects of the present invention more clearly understood, the following is a detailed description by listing specific embodiments. Unless otherwise defined, the technical and scientific terms used herein have the same meanings as those in the technical field to which this application belongs.
[0065] Because the existing packaging materials have poor water vapor barrier properties, the electronic components inside the assembly are exposed to water vapor and oxygen in the air, which reduces the photoelectric conversion rate. The electronic components slowly oxidize and form a crust after oxygen enters, and even affect the life of the assembly. After extensive and in-depth research, the inventors found that the sealant composed of butyl rubber, polyisobutylene composition, thermoplastic elastomer (preferably one or more of SEBS, SEPS, EVOH and POE), reinforcing materials, inorganic fillers, barrier fillers (reduced iron powder and / or molecular sieves), coupling agents, light stabilizers and antioxidants has a good oxygen barrier effect, especially when EVOH and POE are selected as thermoplastic elastomers and reduced iron powder and molecular sieves are used as barrier fillers, the water vapor and oxygen barrier performance is optimal. Based on this, the present invention is completed.
[0066] As used herein, the term "and / or" refers to any one of the optional items or a combination of any two or more of the optional items.
[0067] As used herein, the term "comprising" or "including" means including the described elements, integers or steps, but does not exclude any other elements, integers or steps. In the present invention, when the term "comprising" or "including" is used, unless otherwise specified, the situation consisting of the described elements, integers or steps is also covered.
[0068] As used herein, the term "consisting of" is intended to exclude any element or combination of elements, and any element or combination of elements in any amount, that would alter the basic and novel characteristics of the present invention.
[0069] As used herein, the term "butyl rubber" is understood to mean homopolymers of isobutylene or copolymers of isobutylene and isoprene, which butyl rubber is included in the diene elastomers, as well as halogenated derivatives of these homopolymers and of copolymers of isobutylene and isoprene, in particular, the halogenated derivatives being generally brominated or chlorinated derivatives, for example, isobutylene rubber, copolymers of isobutylene and isoprene (IIR), brominated butyl rubbers, such as brominated isobutylene / isoprene copolymers (BIIR), chlorobutyl rubbers, such as chloroisobutylene / isoprene copolymers (CIIR), and mixtures of the latter.
[0070] As used herein, the term "thermoplastic elastomer" has a structure between a thermoplastic polymer and an elastomer. They are composed of rigid thermoplastic blocks connected by flexible elastomer blocks, such as polybutadiene, polyisoprene, poly (ethylene / butylene) or polyisobutylene. They are generally triblock elastomers with two rigid segments connected by flexible segments. Rigid and flexible segments can be arranged in a linear manner, in a star-shaped manner or in a branched manner. Typically, each of these segments or blocks includes at least 5 or more, typically more than 10 basic units. For example, ethylene-vinyl alcohol copolymer (EVOH), ethylene-octene copolymer (POE), styrene / ethylene-butylene / styrene copolymer (SEBS), styrene / ethylene-propylene / styrene copolymer (SEPS). As used herein, "interpolymer" means a polymer prepared by polymerizing at least two different monomers. The general term "interpolymer" includes the term "copolymer" (which is generally used to refer to a polymer prepared from two different monomers) and the term "terpolymer" (which is generally used to refer to a polymer prepared from three different monomers). It also includes polymers made by polymerizing four or more monomers. "Blend" means a polymer formed by mixing two or more polymers together by physical or chemical methods.
[0071] As used herein, the term "silane coupling agent" refers to a low molecular weight organic silicon compound with a special structure, which can chemically bond (couple) with organic and inorganic materials to increase the adhesion of the two materials.
[0072] As used herein, an "antioxidant" is a substance that, when present in a small amount in a polymer system, can retard or inhibit the oxidation process of the polymer, thereby preventing the aging of the polymer and extending its service life.
[0073] The first object of the present invention is to provide a composition, wherein the raw materials for preparing the composition include the following components: butyl rubber, polyisobutylene composition, thermoplastic elastomer, reinforcing material, inorganic filler, barrier filler, coupling agent, light stabilizer and antioxidant;
[0074] Wherein, the thermoplastic elastomer is selected from one or a combination of SEBS, SEPS, EVOH and POE;
[0075] The barrier filler is selected from reduced iron powder and / or molecular sieve.
[0076] In certain embodiments, the thermoplastic elastomer is EVOH and / or POE.
[0077] In a preferred embodiment, the thermoplastic elastomer is EVOH and POE.
[0078] In some embodiments, the weight ratio of EVOH to POE is 1:(0.1-2), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, etc. Under the condition of a suitable weight ratio of EVOH to POE, the water vapor and oxygen barrier properties of the sealant can be better improved and the cost can be reduced.
[0079] In a preferred embodiment, the weight ratio of EVOH to POE is 1:(0.5-1.5).
[0080] In a preferred embodiment, the weight ratio of EVOH to POE is 1:(0.5-1).
[0081] In a preferred embodiment, the weight ratio of EVOH to POE is 1:1.
[0082] In certain embodiments, the ethylene content in the EVOH is 25 to 35 mass%, for example, 26 mass%, 27 mass%, 28 mass%, 29 mass%, 30 mass%, 31 mass%, 32 mass%, 33 mass%, 34 mass%, 35 mass%, etc.
[0083] In certain embodiments, the ethylene content in the EVOH is 30% by mass, wherein the vinyl alcohol segment has excellent barrier properties against oxygen.
[0084] In certain embodiments, the EVOH has a softening point of 140°C.
[0085] In certain embodiments, the EVOH is purchased from Japan Kuraray E105 resin.
[0086] In certain embodiments, the POE is purchased from DOW Chemical as ENGAGE 8150.
[0087] In certain embodiments, the molecular sieve is from 3A to 5A molecular sieve.
[0088] In certain embodiments, the molecular sieve is selected from 3A molecular sieves.
[0089] In some embodiments, the weight ratio of the reduced iron powder to the molecular sieve is 1:(0.1-1), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, etc. Under the condition of an appropriate weight ratio of reduced iron powder to molecular sieve, the water vapor and oxygen barrier properties of the sealant can be better improved, especially, the reduced iron powder can slowly react chemically under the conditions of water vapor and oxygen to generate Fe2O3, absorb a small amount of water vapor and oxygen molecules that penetrate the organic molecular chain, improve the barrier properties of the sealant, and reduce the cost.
[0090] In certain embodiments, the weight ratio of the reduced iron powder to the molecular sieve is 1:(0.5-1).
[0091] In certain embodiments, the weight ratio of the reduced iron powder to the molecular sieve is 1:0.6.
[0092] In certain embodiments, the polyisobutylene composition includes a high molecular weight polyisobutylene and a medium molecular weight polyisobutylene.
[0093] In certain embodiments, the number average molecular weight of the high molecular weight polyisobutylene is 500,000 to 2,000,000, and the number average molecular weight of the medium molecular weight polyisobutylene is 10,000 to 300,000.
[0094] In certain embodiments, the number average molecular weight of the high molecular weight polyisobutylene is 500,000 to 1,000,000, and the number average molecular weight of the medium molecular weight polyisobutylene is 50,000 to 200,000.
[0095] In certain embodiments, the weight ratio of the high molecular weight polyisobutylene to the medium molecular weight polyisobutylene is 1:(1-10), for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7: 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10, etc.
[0096] In a preferred embodiment, the weight ratio of the high molecular weight polyisobutylene to the medium molecular weight polyisobutylene is 1:(3-8).
[0097] In a preferred embodiment, the weight ratio of the high molecular weight polyisobutylene to the medium molecular weight polyisobutylene is 1:(3-6).
[0098] In certain embodiments, the reinforcing material includes one or a combination of carbon black, fumed silica, and nano-calcium carbonate.
[0099] In a preferred embodiment, the reinforcing material is carbon black. Selecting a suitable reinforcing material can increase strength to improve UV resistance.
[0100] In a preferred embodiment, the carbon black is selected from Cabot N330.
[0101] In certain embodiments, the inorganic filler includes one or a combination of microsilica powder, talc, organic bentonite and nano calcium carbonate.
[0102] In certain embodiments, the inorganic filler is one or a combination of microsilica powder, talc, and organic bentonite.
[0103] In a preferred example, the inorganic filler is a combination of microsilica powder, talcum powder, and organic bentonite.
[0104] In certain embodiments, the weight ratio of the microsilica powder, talc, and organic bentonite is 1: (0.5-2): (0.5-2), for example, 1: 1: 0.5, 1: 1.1: 0.5, 1: 1.2: 0.5, 1: 1.3: 0.5, 1: 1.4: 0.5, 1: 1.5: 0.5, 1: 1.6: 0.5, 1: 1.7: 0.5, 1: 1.8: 0.5, 1: 1: 0.6, 1: 1.1: 0.6, 1: 1.2: 0.6, 1: 1.3: 0.6, 1: 1.4: 0.5 :1.4:0.6, 1:1.5:0.6, 1:1.6:0.6, 1:1.7:0.6, 1:1.8:0.6, 1:1:0.7, 1:1.1:0.7, 1:1.2:0.7, 1:1.3:0.7, 1:1.4:0.7, 1:1.5:0.7, 1:1.6:0.7, 1:1.7:0.7, 1:1.8:0.7, 1:1:1, 1:1.2:1, 1:1.3:1, 1:1.4:1, 1:1.5:1, etc. Under the condition of appropriate weight ratio of microsilica powder, talc powder and organic bentonite, the water vapor and oxygen barrier properties of the sealant can be better improved, the cost can be reduced, and the cold flow of polyisobutylene can be effectively slowed down.
[0105] In certain embodiments, the weight ratio of the microsilica powder, talc, and organic bentonite is 1:(1-2):(0.5-1.5).
[0106] In certain embodiments, the coupling agent is a silane coupling agent.
[0107] In certain embodiments, the coupling agent is one or a combination of vinyl silane coupling agent, methoxy silane coupling agent or isocyanate silane coupling agent.
[0108] In a preferred embodiment, the coupling agent is an isocyanate silane coupling agent. In the present invention, the isocyanate silane coupling agent is not limited, and can achieve the present invention, for example, selected from 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl triethoxy silane, 3-isocyanate propyl methyl dimethoxy silane or 3-isocyanate propyl methyl diethoxy silane. In the present invention, the source of the isocyanate silane coupling agent is not limited, for example, it can be purchased from Ziyue KBE-9007.
[0109] In certain embodiments, the butyl rubber content is 5 to 20 parts by weight, for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.
[0110] In a preferred embodiment, the content of the butyl rubber is 5 to 15 parts.
[0111] In certain embodiments, the raw Mooney viscosity ML1+8 of the butyl rubber is 46-56.
[0112] In certain embodiments, the polyisobutylene composition is present in an amount of 15 to 35 parts by weight, for example, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, etc.
[0113] In certain embodiments, the content of the polyisobutylene composition is 15 to 30 parts.
[0114] In certain embodiments, the content of the thermoplastic elastomer is 5 to 20 parts by weight, for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.
[0115] In a preferred embodiment, the content of the thermoplastic elastomer is 5 to 15 parts.
[0116] In certain embodiments, the content of the reinforcing material is 1 to 10 parts by weight, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.
[0117] In a preferred embodiment, the content of the reinforcing material is 2 to 8 parts.
[0118] In certain embodiments, the content of the inorganic filler is 40 to 55 parts by weight, for example, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, etc.
[0119] In a preferred embodiment, the content of the inorganic filler is 40 to 50 parts.
[0120] In certain embodiments, the barrier filler is present in an amount of 2 to 10 parts by weight, for example, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.
[0121] In a preferred embodiment, the content of the barrier filler is 5 to 10 parts.
[0122] In certain embodiments, the coupling agent is present in an amount of 0.1 to 2 parts by weight, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, etc.
[0123] In a preferred embodiment, the content of the coupling agent is 0.5 to 1.5 parts. Under the condition of appropriate weight percentage of the coupling agent, the bonding force between the adhesive and the inorganic interface material can be increased, the water vapor and oxygen barrier properties of the sealant can be better improved, and the yellowing resistance, less volatility and lower cost can be achieved.
[0124] In certain embodiments, the content of the light stabilizer is 0.1 to 1 part by weight, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0125] In a preferred embodiment, the content of the light stabilizer is 0.1 to 0.8 parts.
[0126] In certain embodiments, the antioxidant is present in an amount of 0.1 to 1 part by weight, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0127] In a preferred embodiment, the content of the antioxidant is 0.1 to 0.8 parts.
[0128] In certain embodiments, the raw materials for preparing the composition include: butyl rubber, high molecular weight polyisobutylene, medium molecular weight polyisobutylene, EVOH, POE, organic bentonite, talc, microsilica powder, carbon black, reduced iron powder, 3A molecular sieve, coupling agent, light stabilizer and antioxidant;
[0129] In certain embodiments, the raw materials for preparing the composition consist of butyl rubber, high molecular weight polyisobutylene, medium molecular weight polyisobutylene, EVOH, POE, organic bentonite, talc, microsilica powder, carbon black, reduced iron powder, 3A molecular sieve, coupling agent, light stabilizer and antioxidant.
[0130] In certain embodiments, the composition is prepared from raw materials including:
[0131]
[0132]
[0133] In certain embodiments, the composition is prepared from raw materials including:
[0134]
[0135] In certain embodiments, the composition is prepared from raw materials including:
[0136]
[0137]
[0138] The second object of the present invention is to provide a method for preparing the sealant as described in any one of the above items, the preparation method comprising the following steps:
[0139] (1) adding butyl rubber, polyisobutylene composition, and thermoplastic elastomer into a kneader according to weight proportions, heating, and kneading under the protection of an inert gas, and then adding a reinforcing material, an inorganic filler, a light stabilizer, and an antioxidant into the kneader and continuing to knead;
[0140] (2) Then, the coupling agent and barrier filler are added to the mixture obtained in step (1), the inert gas is turned off, and the mixture is evacuated for kneading, and the vacuum degree is controlled to be 0.08-0.1 MPa.
[0141] In certain embodiments, before step (1), the inorganic filler, the reinforcing material and the barrier filler are first dried and dehydrated.
[0142] In certain embodiments, the kneading temperature in step (1) is controlled to be 140-160°C (specifically preferably 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C, 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C, 160°C, etc.), and the rotation speed is 20-30r / min.
[0143] In certain embodiments, the kneading time in step (1) is controlled to be 25 to 35 min, for example, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, etc.
[0144] In certain embodiments, the kneading time in step (1) is controlled to be 30 to 40 minutes.
[0145] In certain embodiments, the kneading temperature in step (2) is controlled to be 140-160°C (specifically preferably 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C, 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C, 160°C, etc.), and the rotation speed is 20-30r / min.
[0146] In certain embodiments, the kneading time in step (2) is controlled to be 35 to 45 min, for example, 36 min, 37 min, 38 min, 39 min, 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, etc.
[0147] In certain embodiments, the kneading time in step (2) is controlled to be 30 to 40 minutes.
[0148] The preparation method of the sealant of the present invention comprises the following steps:
[0149] (1) Dehydrate the inorganic filler, barrier filler, and reinforcing material in a vacuum dryer at 105°C for more than 60 minutes;
[0150] (2) adding butyl rubber, polyisobutylene composition and thermoplastic elastomer according to weight proportions into a clean kneader, raising the temperature of the kneader to 140-160° C., covering the kneader with a cover plate and introducing nitrogen to maintain the kneader speed at 20 r / min for kneading and mixing for 30 minutes, then adding reinforcing material, inorganic filler, light stabilizer and antioxidant into the kneader, maintaining the above temperature and speed and continuing kneading for 30 minutes;
[0151] (3) Then add the coupling agent and barrier filler according to the weight proportions to the mixture obtained in step (2), and weigh and add the molecular sieve, tackifying resin, coupling agent, and reduced iron powder in turn according to the addition ratio. Close the nitrogen channel, evacuate and maintain the vacuum degree at 0.08-0.1MPa, increase the temperature to 140°C, set the speed to 20r / min and knead and mix for 30 minutes. After observing that the sealant in the kneader is mixed evenly without particles and agglomerates, extrude the material through the single screw of the kneader and vacuum-pack it with aluminum-plastic film, and add a moisture-absorbing drying bag in the packaging bag. The preparation method provided by the present invention can greatly reduce the contact between each component and water and oxygen.
[0152] The third object of the present invention is to provide an application of the composition described above or the composition obtained by the preparation method described above in oxygen-barrier hot-melt sealant, especially in photovoltaic cell packaging.
[0153] The present invention is further described below in conjunction with specific examples and comparative examples. If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. Unless otherwise specified, various starting materials, materials and reagents are commercially available or synthesized according to known methods.
[0154] In the present application, the light stabilizer is RIASORB UV-326 (purchased from Rianlon) or RIASORB UV-770 (hindered amines); the antioxidants are BASF 1010 (phosphites) and BASF 168 (thioesters).
[0155] Example 1
[0156] The sealant is prepared according to the above preparation method. The specific selection of each raw material is shown in the following table:
[0157] Components Mass fraction Butyl rubber 14 Medium molecular weight polyisobutylene 26 Macromolecular polyisobutylene 5 Silica powder 14 talcum powder 20 Organic bentonite 14 Carbon Black 5 Coupling agent 1 Light Stabilizer 0.5 Antioxidants 0.5 total 100
[0158] Example 2
[0159] Except for the different raw material composition, it is basically the same as Example 1. For the specific selection of each raw material, please refer to the following table:
[0160] Components Mass fraction Butyl rubber 10 Medium molecular weight polyisobutylene 20 Macromolecular polyisobutylene 5 Evoh 10 Silica powder 14 talcum powder 20 Organic bentonite 14 Carbon Black 5 Coupling agent 1 Light Stabilizer 0.5 Antioxidants 0.5 total 100
[0161] Example 3
[0162] Except for the different raw material composition, it is basically the same as Example 1. For the specific selection of each raw material, please refer to the following table:
[0163] Components Mass fraction Butyl rubber 10 Medium molecular weight polyisobutylene 20 Macromolecular polyisobutylene 5 POE 10 Silica powder 14 talcum powder 20 Organic bentonite 14 Carbon Black 5 Coupling agent 1 Light Stabilizer 0.5 Antioxidants 0.5 total 100
[0164] Example 4
[0165] Except for the different raw material composition, it is basically the same as Example 1. For the specific selection of each raw material, please refer to the following table:
[0166] Components Mass fraction Butyl rubber 10 Medium molecular weight polyisobutylene 20 Macromolecular polyisobutylene 5 POE 5 Evoh 5 Silica powder 14 talcum powder 20 Organic bentonite 14 Carbon Black 5 Coupling agent 1 Light Stabilizer 0.5 Antioxidants 0.5 total 100
[0167] Example 5
[0168] Except for the different raw material composition, it is basically the same as Example 1. For the specific selection of each raw material, please refer to the following table:
[0169] Components Mass fraction Butyl rubber 10 Medium molecular weight polyisobutylene 20 Macromolecular polyisobutylene 5 POE 5 Evoh 5 Silica powder 12 talcum powder 16 Organic bentonite 12 Reduced iron powder 5 Molecular sieve 3 Carbon Black 5 Coupling agent 1 Light Stabilizer 0.5 Antioxidants 0.5 total 100
[0170] Example 6
[0171] Except for the different raw material composition, it is basically the same as Example 1. For the specific selection of each raw material, please refer to the following table:
[0172] Components Mass fraction Butyl rubber 10 Medium molecular weight polyisobutylene 20 Macromolecular polyisobutylene 5 POE 5 Evoh 5 Silica powder 12 talcum powder 16 Organic bentonite 12 Reduced iron powder 8 Carbon Black 5 Coupling agent 1 Light Stabilizer 0.5 Antioxidants 0.5 total 100
[0173] Example 7
[0174] Except for the different raw material composition, it is basically the same as Example 1. For the specific selection of each raw material, please refer to the following table:
[0175]
[0176]
[0177] Comparative Example 1: Commercially available silicone sealant - Loctite RTV5900.
[0178] Comparative Example 2: Commercially available butyl sealant - Kangda New Materials WD216.
[0179] Performance Testing
[0180] 1. Ultraviolet radiation resistance test: In order to verify the ultraviolet radiation resistance of the sealant, the ultraviolet resistance test is carried out according to the ultraviolet pretreatment test method of IEC61345;
[0181] 2. Determination of glass-to-glass tensile shear strength: Test the tensile shear strength of sealant according to the national standard GB / T 7124-2008 test method;
[0182] 3. Determination of water vapor transmission rate: Test the water vapor transmission rate of sealant according to the national standard GB / T 21529-2008 test method;
[0183] 4. Determination of oxygen permeability: The oxygen permeability of the sealant is tested according to the national standard GB / T19789-2005 test method.
[0184] The test results are shown in the table below:
[0185]
[0186] It can be seen from the above table that the sealant provided in the present invention produces a synergistic effect by adding different components and adjusting the weight ratio of each component, thereby ensuring the stability of the barrier performance, weather resistance and bonding strength, and can effectively meet the requirements for long-term outdoor water vapor and oxygen barrier effects.
[0187] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A composition, characterized in that The raw materials for preparing the composition include the following components: butyl rubber, polyisobutylene composition, thermoplastic elastomer, reinforcing material, inorganic filler, barrier filler, coupling agent, light stabilizer and antioxidant; Wherein, the thermoplastic elastomer is selected from one or a combination of SEBS, SEPS, EVOH and POE; The barrier filler is selected from reduced iron powder and / or molecular sieve.
2. The composition according to claim 1, characterized in that The thermoplastic elastomer is EVOH and / or POE, preferably a combination of EVOH and POE; Preferably, the weight ratio of the EVOH to the POE is 1:(0.1-2), preferably 1:(0.5-1.5); Preferably, the ethylene content in the EVOH is 25 to 35% by mass.
3. The composition according to claim 1 or 2, characterized in that The molecular sieve is selected from 3A to 5A molecular sieve; Preferably, the weight ratio of the reduced iron powder to the molecular sieve is 1:(0.1-1), preferably 1:(0.5-1).
4. The composition according to any one of claims 1 to 3, characterized in that The polyisobutylene composition comprises high molecular weight polyisobutylene and medium molecular weight polyisobutylene; Preferably, the number average molecular weight of the high molecular weight polyisobutylene is 500,000 to 2,000,000, and the number average molecular weight of the medium molecular weight polyisobutylene is 10,000 to 300,000; Preferably, the weight ratio of the high molecular weight polyisobutylene to the medium molecular weight polyisobutylene is 1:(1-10), preferably 1:(3-8).
5. The composition according to any one of claims 1 to 4, characterized in that The reinforcing material comprises one or a combination of carbon black, fumed silica, and nano calcium carbonate, preferably carbon black; Preferably, the inorganic filler comprises one or more of microsilica powder, talc, organic bentonite and nano calcium carbonate, preferably one or more of microsilica powder, talc, organic bentonite, more preferably a combination of microsilica powder, talc, organic bentonite; Preferably, the weight ratio of the microsilica powder, talc and organic bentonite is 1:(0.5-2):(0.5-2), preferably 1:(1-2):(0.5-1.5); Preferably, the coupling agent is a silane coupling agent, preferably one or a combination of vinyl silane coupling agent, methoxy silane coupling agent or isocyanate silane coupling agent, more preferably an isocyanate silane coupling agent.
6. The composition according to any one of claims 1 to 5, characterized in that The content of the butyl rubber is 5 to 20 parts by weight, preferably 5 to 15 parts; and / or, the content of the polyisobutylene composition is 15 to 35 parts, preferably 15 to 30 parts; and / or, the content of the thermoplastic elastomer is 5 to 20 parts, preferably 5 to 15 parts; and / or, the content of the reinforcing material is 1 to 10 parts, preferably 2 to 8 parts; And / or, the content of the inorganic filler is 40 to 55 parts, preferably 40 to 50 parts; and / or, the content of the barrier filler is 2 to 10 parts, preferably 5 to 10 parts; And / or, the content of the coupling agent is 0.1 to 2 parts, preferably 0.5 to 1.5 parts; and / or, the content of the light stabilizer is 0.1 to 1 part, preferably 0.1 to 0.8 part; And / or, the content of the antioxidant is 0.1 to 1 part, preferably 0.1 to 0.8 part.
7. The composition according to any one of claims 1 to 6, characterized in that The raw materials for preparing the composition include: butyl rubber, high molecular weight polyisobutylene, medium molecular weight polyisobutylene, EVOH, POE, organic bentonite, talc, microsilica powder, carbon black, reduced iron powder, 3A molecular sieve, coupling agent, light stabilizer and antioxidant; Preferably, the raw materials for preparing the composition consist of butyl rubber, high molecular weight polyisobutylene, medium molecular weight polyisobutylene, EVOH, POE, organic bentonite, talc, microsilica powder, carbon black, reduced iron powder, 3A molecular sieve, coupling agent, light stabilizer and antioxidant.
8. The composition according to claim 7, characterized in that The raw materials for preparing the composition include: Preferably, the raw materials for preparing the composition include:
9. A method for preparing the composition according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) adding butyl rubber, polyisobutylene composition, and thermoplastic elastomer into a kneader according to weight proportions, heating, and kneading under the protection of an inert gas, and then adding a reinforcing material, an inorganic filler, a light stabilizer, and an antioxidant into the kneader and continuing to knead; (2) then adding the coupling agent and barrier filler to the mixture obtained in step (1), closing the inert gas and evacuating the mixture for kneading, and controlling the vacuum degree to be 0.08 to 0.1 MPa; Preferably, before step (1), the inorganic filler, the reinforcing material and the barrier filler are first dried and dehydrated; Preferably, the kneading temperature in step (1) is controlled to be 140-160° C. and the rotation speed is 20-30 r / min; Preferably, the kneading time in step (1) is controlled to be 25 to 35 minutes, preferably 30 to 40 minutes; Preferably, the kneading temperature in step (2) is controlled to be 140-160° C. and the rotation speed is 20-30 r / min; Preferably, the kneading time in step (2) is controlled to be 35 to 45 minutes, preferably 30 to 40 minutes.
10. Use of the composition according to claims 1 to 8 or the composition obtained by the preparation method according to claim 9 in oxygen-barrier hot-melt sealant.